2014
DOI: 10.1371/journal.pone.0110559
|View full text |Cite
|
Sign up to set email alerts
|

FoxA4 Favours Notochord Formation by Inhibiting Contiguous Mesodermal Fates and Restricts Anterior Neural Development in Xenopus Embryos

Abstract: In vertebrates, the embryonic dorsal midline is a crucial signalling centre that patterns the surrounding tissues during development. Members of the FoxA subfamily of transcription factors are expressed in the structures that compose this centre. Foxa2 is essential for dorsal midline development in mammals, since knock-out mouse embryos lack a definitive node, notochord and floor plate. The related gene foxA4 is only present in amphibians. Expression begins in the blastula –chordin and –noggin expressing centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Finally, in Xenopus , foxa4 is the earliest and most abundantly expressed foxa gene during early mesendoderm specification. However, Foxa4's role in early mesendoderm development is not known, although by early neurula stages it promotes notochord formation and inhibits prechordal and paraxial mesoderm [132]. Our network analysis reveals that foxa4 is activated by Smad2/3, via a Foxh1-independent mechanism [26].…”
Section: Core Zygotic Mesendoderm Transcription Factorsmentioning
confidence: 99%
“…Finally, in Xenopus , foxa4 is the earliest and most abundantly expressed foxa gene during early mesendoderm specification. However, Foxa4's role in early mesendoderm development is not known, although by early neurula stages it promotes notochord formation and inhibits prechordal and paraxial mesoderm [132]. Our network analysis reveals that foxa4 is activated by Smad2/3, via a Foxh1-independent mechanism [26].…”
Section: Core Zygotic Mesendoderm Transcription Factorsmentioning
confidence: 99%
“…3 D); b) a posterior subdomain, corresponding to the notochordal cells (red arrow, Fig. 3 D), which ultimately form a rod by convergent-extension movements ( Murgan et al, 2014 ; Kwan and Kirschner, 2003 ). Cer-S- injected embryos showed that most chrd.1 expression consisted of the fan-shaped subdomain (green arrow, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rostral forebrain is an evolutionary acquisition of vertebrates related to the appearance of the Hesx1 gene at the beginning of vertebrate evolution ( Ermakova et al, 1999 ; Wilson and Houart, 2004 ; Ermakova et al, 2007 ; Bayramov et al, 2016 ) and derives entirely from the BCNE center ( Kuroda et al, 2004 ). We have previously shown that expression of the rostral forebrain regulator hesx1 persists after blocking Nodal signaling in Xenopus ( Murgan et al, 2014 ). Indeed, the expansion of the Hesx1 domain in Nodal −/− mouse embryos occurred before gastrulation ( Camus et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-mount in-situ hybridization was performed with digoxigeninlabeled probes (Harland, 1991) to muscle actin (MA) and myod (Keren et al, 2005), chd (Murgan et al, 2014), and otx2, krox20 and hoxb9 (Aamar and Frank, 2004;Gutkovich et al, 2010).…”
Section: In-situ Hybridizationmentioning
confidence: 99%